The Eurozone Crisis : A Historical Lesson and Future Prospects - Babich, Maria (2019)
The Eurozone crisis – a European disaster which broke out a decade ago. The crisis left deep scars on many countries and made the future of the European integration questionable. Structural flaws in the institutional design of the EMU, governance problem, decision-making issues, – this is not the full list of causes and factors which worsened the crisis and made it comparable to the Great Depression.But some lessons have learned. New institutions were set, new regulations were implemented and regulation was strengthened. And nowadays all the efforts are focused on completing the Banking Union, which is essential for the future of the EMU and for a financial system.